2010
DOI: 10.1086/652442
|View full text |Cite
|
Sign up to set email alerts
|

A Large Q Fever Outbreak in an Urban School in Central Israel

Abstract: BACKGROUND. On 28 June 2005, numerous cases of febrile illness were reported among 322 students and employees of a boarding high school located in an urban area in central Israel. Subsequent investigation identified a large outbreak of Q fever which started 2 weeks earlier. We describe the investigation of this outbreak and its possible implications. METHODS. We conducted a case-control study to identify risk factors for Q fever disease. Environmental sampling was conducted to identify the source and the mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 21 publications
0
54
0
2
Order By: Relevance
“…The three other studies reported the presence of C. burnetii DNA in dust (17) or primarily soil samples from a geographically large area in the United States (11,14). The latter three studies investigated the presence of C. burnetii DNA in soil samples (6) and surface swabs (1,9) in relation to human Q fever outbreaks.…”
mentioning
confidence: 99%
“…The three other studies reported the presence of C. burnetii DNA in dust (17) or primarily soil samples from a geographically large area in the United States (11,14). The latter three studies investigated the presence of C. burnetii DNA in soil samples (6) and surface swabs (1,9) in relation to human Q fever outbreaks.…”
mentioning
confidence: 99%
“…In Israel the average annual incidence of Q fever is 0.6 cases per 100,000 persons, and several outbreaks have been reported in the past, including an urban outbreak (Amitai et al 2010). Endocarditis is the most severe and potentially fatal form of chronic Q fever, with an overall 10-year mortality of 27% (Million et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Les principales cellules cibles sont les macrophages (lymphe et ganglions lymphatiques, rate, foie, poumons…), les monocytes circulant du sang (Baca et Paretsky 1983) et les trophoblastes (Ben Amara et al 2010). Son existence dans des amibes libres a également été décrite (La Scola et Raoult 2001;Amitai et al 2010) ainsi que sa persistance dans les adipocytes murins (Bechah et al 2014). La division de C. burnetii est complexe et caractérisée par la présence de 2 formes morphologiques correspondant à différentes phases de développement : -Les variants de petite taille (en anglais « small cell variant »), mesurent de 0,2 à 0,5 m, et sont denses en microscopie électronique.…”
Section: Différenciation Cellulaireunclassified